Bowel Preparation for Small Bowel Capsule Endoscopy: Is There Still a Role for Polyethylene Glycol? - Collins, Paul; Haslam, Neil; Morris, Anthony; Skouras, Thomas; Bond, Ashley (Journal of Digestive Endoscopy, 2020)
Objectives This study aimed to assess the impact of polyethylene glycol (PEG) bowel cleansing on performance characteristics of small bowel capsule endoscopy (SBCE).Materials and Methods Data from consecutive patients undergoing SBCE in the period before and after the introduction of PEG 2 L bowel cleansing with PEG were collated retrospectively. The indication, diagnostic yield (DY), clinical outcome, small bowel transit time, gastric transit time, and completion rate were recorded for each procedure.Results Data from 286 patients were analyzed. PEG 2 L was not superior to 12-hour fasting for DY (66 [53%] vs. 76 [47%] patients [p = 0.348]), or DY for significant findings (findings requiring a further intervention or investigation; 29 [23%] vs. 52 [32%] patients [p = 0.090]).There was a trend toward an increased DY for significant findings in patients undergoing investigation for iron-deficiency anemia (IDA) receiving PEG 2 L that just failed to meet statistical significance (13 [31%] and 25 [21%] patients, respectively [p = 0.06]). Transit times and completion rates were unaffected by bowel cleansing.Conclusion Bowel cleansing with PEG 2 L is not superior to fasting for overall DY in SBCE. PEG 2 L may confer an advantage for the detection of significant lesions in patient with IDA. Further investigation of optimal modes of bowel preparation is indicated.
Keywords: bowel cleansing; bowel preparation; small bowel capsule endoscopy; iron-deficiency anemia